Impact of neoadjuvant radiation on margins for non–squamous cell carcinoma sinonasal malignancies. (16th October 2018) - Fu, Terence; Chin, Christopher J.; Xu, Wei; Che, Jiahua; Huang, Shao Hui; Monteiro, Eric; Alghonaim, Yazeed; Ringash, Jolie; Witterick, Ian J.
Abstract : Objectives/Hypothesis: Treatment of non–squamous cell carcinoma sinonasal malignancies (NSCCSMs) typically involves surgery and radiotherapy (RT), but optimal sequencing remains controversial. Study Design: Retrospective chart review. Methods: Patients with NSCCSM treated with combined surgery and RT between 2000 and 2011 were identified. Margin control, overall survival, disease‐free survival, local recurrence‐free survival, and regional recurrence‐free survival were compared between neoadjuvant and adjuvant RT groups. Results: Eight‐four patients were included (23 neoadjuvant and 61 adjuvant RT). A higher proportion of patients receiving neoadjuvant RT achieved negative/close resection margins compared to those receiving adjuvant RT (83% vs. 41%, P = .003). Multivariable analysis also showed that neoadjuvant RT was associated with an 81% decreased odds of positive margins odds ratio: 0.19, 95% confidence interval: 0.05‐0.77, P = .02). Conclusions: Neoadjuvant RT may be associated with improved margin status among patients with NSCCSM treated with surgery and RT. Future prospective studies with larger, more homogeneous populations are needed to clarify optimal treatment strategies. Level of Evidence: 4 Laryngoscope, 128:2796–2803, 2018